Relationship between the genetic polymorphisms of vicR and vicK Streptococcus mutans genes and early childhood caries in two-year-old children - Zhuang, Pei Lin (BMC Oral Health, 2018)
BACKGROUND: The VicRK two-component signalling system regulates virulence and cariogenicity in Streptococcus mutans (S. mutans). The purpose of this study was to explore the genetic polymorphisms of the vicR and vicK genes, which are associated with dental caries in children with S. mutans. METHODS: In this study, 121 (from each group) clinical S. mutans strains were isolated from caries-free children and children with high-severity caries to sequence the vicR and vicK genes. Genomic DNA was extracted from S. mutans strains and amplified using PCR. The PCR products were purified and sequenced. A chi-squared test and ABI Variant Reporter software were used to analyse the sequencing results. RESULTS: The 242 clinically isolated S. mutans strains contained the full-length vicR and vicK genes. No nucleotide sequence insertions or deletions were observed in the two genes. Four silent point mutations were identified in the vicR genes, and no missense mutations could be detected. Forty-one mutations were identified in the vicK genes. In addition to 32 silent mutations, 9 missense mutations at the 173, 337, 470, 1051, 1132, 1258, 1260, 1277, and 1348 bp positions were found. The distribution frequencies of the missense mutations were not significantly different between the groups, except for the C470T mutation. The frequency of the C470T missense mutation was higher in the high-severity caries group than in the caries-free group. CONCLUSIONS: vicR sequences are highly conserved in S. mutans clinical isolates. The locus 470 missense mutation of the vicK gene may be related to caries in children with S. mutans.